Segment‐Specific Distal Crural Artery Intima–Media Thickness and Systemic Inflammatory Markers in Thromboangiitis Obliterans - Oğuzhan Türksayar; Ali Dablan; Abdurrezzak Şendur; Mustafa Fatih Arslan; Mehmet Cingöz; Çağrı Erdim; Tevfik Güzelbey; Özgür Kılıçkesmez (Journal of Clinical Ultrasound, 2026)
ABSTRACT Background To compare segment‐specific lower‐extremity arterial intima–media thickness (IMT) between patients with thromboangiitis obliterans (TAO) and smoking‐comparable controls using B‐mode ultrasonography, and to assess associations with inflammatory parameters. Methods This prospective case‐control study included 22 male patients with angiographically confirmed, intervention‐treated TAO and 22 healthy male volunteers with comparable age and cumulative smoking exposure. IMT was measured at the popliteal artery, anterior tibial artery (ATA), and posterior tibial artery (PTA). Hemogram‐derived indices, C‐reactive protein, and erythrocyte sedimentation rate were recorded. Intra‐ and inter‐observer reproducibility were assessed. Primary IMT comparisons were adjusted for age and cumulative smoking exposure, with Holm correction applied separately to the IMT and inflammatory‐marker comparisons; Benjamini–Hochberg correction was used for Spearman analyses. Results ATA and PTA IMT were greater in patients with TAO and remained significant after adjustment for age and cumulative smoking exposure and correction for multiple comparisons (both Holm‐adjusted p < 0.001). Popliteal IMT did not differ ( p = 0.625). CRP and ESR remained higher after correction, whereas NLR did not (adjusted p = 0.066). Conclusion Clinically stable TAO was associated with greater distal crural IMT without significant popliteal IMT difference. Distal crural B‐mode IMT measurement may provide complementary structural information in TAO.